A New Dual-Band, Dual-Polarized and Single Feed Reconfigurable Antenna - Sedghara, A.; Atlasbaf, Z. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a new single feed reconfigurable annular-ring slot antenna for polarization and frequency diversity for WLAN and WiMAX applications is proposed. This antenna has a simple structure; it contains two concentric circular slots, and four tuning stubs on one side of the substrate, and a 50 ? microstrip feed line and two stubs on the other side. The proposed antenna can be switched between two resonant frequencies, 2.4 GHz (WLAN) and 3.5 GHz (WiMAX). Furthermore, it can be switched between left-hand circular polarization (LHCP) and right-hand circular polarization (RHCP) at both resonant frequencies. Using seven switches (PIN diode), on both sides of the substrate. Details of the antenna design are shown and the results are also exhibited and discussed. Simulation and experimental results indicate that the proposed antenna demonstrates a good impedance bandwidth at the two resonant frequencies, and satisfactory axial ratios in the circularly polarized states.